Strength work and strength endurance Part 1 - Ryabov, Sergey N.; Funtikov, Georgy V. (Физическое воспитание и студенческий спорт, 2023)
The purpose of the research is to study the possibilities of increasing the physical strength of an athlete through special exercises. An increase in endurance during physical exertion in relation to strength sports and martial arts is also separately considered. The physiological aspects of the work of human muscles are analyzed, on which the power traction of the muscle and the possibility of prolonged work under load depend. Myofibrils and mitochondria located in muscle fibers are chosen as the main object of the study. Since the fibers inside the muscle are divided into two main types – i.e. “fast” and “slow” – and it is believed that fast fibers are much stronger than slow ones, and slow ones are more enduring than fast ones, different training methods are offered for those and others. The directions of the training process for increasing physical strength and strength endurance are determined.